The Relationship Between Parenting Styles and Mental Health Among Junior High School Adolescents - Muhammad Romadhon; Ria Wulandari; Rinni Gusanti (International Journal of Health Engineering and Technology, 2026)
Adolescent mental health is a growing public health concern due to the increasing prevalence of psychological disorders among school-aged populations. One of the important factors influencing adolescents’ mental health development is parenting style. This study aimed to determine the relationship between parenting styles and mental health among junior high school adolescents. This study employed a quantitative approach with a cross-sectional design. The study population consisted of all students of SMP Muhammadiyah in the working area of the Kemalaraja Public Health Center, Ogan Komering Ulu Regency, in 2025, totaling 44 students. All students were included as respondents using a total sampling technique. Data were collected using a parenting style questionnaire and the DASS-21 instrument to assess adolescents’ mental health. Data analysis was conducted using univariate and bivariate analyses with the Chi-Square test at a significance level of 0.05. The results showed that most respondents experienced a democratic parenting style (38.6%), and the majority of adolescents were categorized as having poor mental health (59.1%). Statistical analysis indicated a significant relationship between parenting style and adolescents’ mental health (p = 0.003). This study concludes that parenting style is significantly associated with adolescents’ mental health. Therefore, collaborative efforts involving parents, schools, and health services are needed to improve adolescents’ mental health outcomes.